Methodology of knowledge acquisition for machinery diagnostics - Moczulski, Wojciech (Computer Assisted Methods in Engineering and Science, 2023)
The paper deals with a comprehensive methodology concerning knowledge acquisition on machinery for the purpose of expert systems suitable for aiding of diagnostic inference. ·The methodology includes selected methods of diagnostic knowledge representation, methods of knowledge acquisition from domain experts and from preclassified examples, methods of assessment of previously acquired knowledge and a scenario of knowledge acquisition process. All the methods have been implemented in a Knowledge Acquisition System. Moreover, some examples of applications of the elaborated methodology have been given.